Comparison of Charge Nurses’ and Registered Nurses’ Perceptions of Management Functions in the Implementation of Supervision in Hospital - Nelly Febriani; Tatiana Siregar (UIMA Press, 2021)
Introduction: Different perceptions in the supervision process, part of the management functions of nurse manager, are at risk and have a bad impact, such as conflicts that will result in lack of motivation, communication barrier, and decreased performance and quality of services in the hospital. Purpose: The purpose of the study was to compare the perception of the head of the room with the implementing nurse about the role and function of management in the implementation of supervision. Methods: This quantitative study was conducted on a population of 515 nurses, and 81 nurses were used as a sample (71 nurses and 7 room heads) which were selected by accidental sampling. The research tool is in the form of a questionnaire containing management functions in supervision. Data were analyzed using independent t-test. Results: The results of this research did not show a significant difference between charge nurses’ and registered nurses’ perceptions of the management function in supervision, as indicated by the p-value> 0.025 (95% CI), p-value = 0.990 (planning), p-value = 0.957 (organizing), p-value=0.962 (staffing), p-value=0.508 (directing), Conclusion: With actuating aspect that obtained p-value = 0.977 and controlling aspect that obtained p-value = 0.790, the conclusion of this research is there was no significant difference between charge nurses’ and registered nurses’ perceptions of management functions in supervision.